Design and simulation a new code with zero cross-correlation for SAC-OCDMA networks - Thanaa Hussein, Abd; Syed Alwee Aljunid, Syed Junid, Prof. Dr.; Hilal Adnan, Fadhil, Dr.; R. Badlishah, Ahmad, Prof. Dr. (INSInet Publications, 2012)
Link to publisher's homepage at http://insipub.com/